Mesenchymal Stem Cell-Conditioned Medium Protects Hippocampal Neurons From Radiation Damage by Suppressing Oxidative Stress and Apoptosis - Yue Huang; Xiaolong Mei; Weishi Jiang; Hui Zhao; Zhenyu Yan; Haixia Zhang; Ying Liu; Xia Hu; Jingyi Zhang; Wenshuo Peng; Jing Zhang; Qingling Qi; et al. (SAGE Publishing, 2021)
Objective: To investigate the effects of mesenchymal stem cell-conditioned medium (MSC-CM) on radiation-induced oxidative stress, survival and apoptosis in hippocampal neurons. Methods: The following groups were defined: Control, radiation treatment (RT), RT+MSC-CM, MSC-CM, RT + N-Acetylcysteine (RT+NAC), and RT + MSC-CM + PI3 K inhibitor (LY294002). A cell Counting Kit-8 (CCK-8) was used to measure cell proliferation. Apoptosis was examined by AnnexinV/PI flow cytometric analyses. Intracellular reactive oxygen species (ROS) were detected by DCFH-DA. Intracellular glutathione (GSH), malondialdehyde (MDA) content, and superoxide dismutase (SOD) activity were detected by colorimetric assays. Protein levels of γ-H2AX, PI3K-AKT, P53, cleaved caspase-3, Bax, and BCl-2 were analyzed by Western blotting. Results: The proliferation of HT22 cells was significantly inhibited in the RT group, but was significantly preserved in the RT + MSC-CM group (P < 0.01). Apoptosis was significantly higher in the RT group than in the RT+ MSC-CM group (P < 0.01). MSC-CM decreased intracellular ROS and MDA content after irradiation (P < 0.01). GSH level and SOD activity were higher in the RT + MSC-CM group than in the RT group, as was MMP (P < 0.01). MSC-CM decreased expression of γ-H2AX, P53, Bax, and cleaved-caspase-3, but increased Bcl-2 expression (P < 0.01). Conclusion: MSC-CM attenuated radiation-induced hippocampal neuron cell line damage by alleviating oxidative stress and suppressing apoptosis.